Killing Custer the Battle of the Little Bighorn and the fate of the Plains Indians - Welch, James 1940-2003; Stekler, Paul Jeffrey (New York Penguin Books, 1994)
Nonfictionalized account, from the Indian point of view, of Custer's attack on the Plains Indians in 1876.
Includes bibliographical references and index.
Keywords: Little Bighorn, Battle of the, Mont., 1876.; Indians of North America -- Wars -- 1866-1895.